Molecular interactions between soybean glycinin (11S) and genistein using spectroscopic and in silico analyses. (May 2023) - Smith, Emelia; Condict, Lloyd; Ashton, John; Kasapis, Stefan
Abstract: Interactions and binding mechanisms between soybean glycinin (11S) and genistein were investigated at near neutral pH (7.4) and ambient temperature using various spectroscopic techniques and molecular docking. Ultra-violet visible spectroscopy revealed non-covalent bonds were responsible for the stabilisation of the complex. Following complexation, minor reductions in the alpha helix and beta sheet content of the protein were confirmed by circular dichroism (CD) and infrared spectroscopy (FTIR). Fluorescence quenching and molecular docking predicted a 11S trimer and genistein complex with a 1:1 stoichiometric ratio, with the binding location predominantly on the interior portion of the protein, stabilised in majority by hydrogen bonds. Although binding was determined to be of moderate strength, secondary structure characterisation suggested that the structural components of the protein remained largely unchanged. This outcome indicates that the ligand can be accommodated in the interior of the 11S trimer, forming a stable complex within the present conditions of neutral pH and ambient temperature. Graphical abstract: 3D image of best binding pose between glycinin and genistein under ambient conditions, with bottom right 2D image depicting interactions with amino acids of the protein and binding distances where dark green lines represent hydrogen bonds, pale green lines represent hydrogen-pi bonds, orange lines represent pi-anion bonds and unbound amino acids interact via non covalent interactions. Image 1 Highlights: Genistein is bound in the interior portion of soybean glycinin (11S). Binding is accommodated with only minor changes to the protein secondary structure. Interactions are stabilised largely by hydrogen bonds and van der Waals forces. Binding stoichiometry of the soy 11S trimer-genistein complex is 1:1.